Factors associated with early girl-child pregnancies in Chidamoyo and Magunje areas of Hurungwe District: Zimbabwe - Nyembesi, Samuriwo; Miriam, Chitura; Sungano, Prof Mharakurwa; Auxillia, Prof Chideme Munodawafa (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2016)
Early girl-child pregnancy occurring in young girls 13-17 years remains a serious health and social problem worldwide and has been associated with many risk factors in the young peoples, family, school and neighbourhoods This study was done to assess factors associated with early girl-child pregnancies in Chidamoyo and Magunje areas of Hurungwe, Zimbabwe, using a case control study design to identify factors that may contribute to early girl-child pregnancies, by comparing subjects who have the early girl-child pregnancy (cases) with subjects who do not have the early girl-child pregnancies, but have their first pregnancies at mature age, but are similar in the fact they are all pregnant women with their first pregnancies. Data were collected from 82 respondents, 4 midwives as key informants and Chidamoyo and Magujne Hospitals Maternity registers. Results showed that independent factors associated with early girl-child pregnancies were a) religion, being of apostolic faith (OR3.34 95%CI 1.35 8.27) were significant religious risk factors associated with early girl-child pregnancies. Low socio-economic status (OR 3.34 95% CI1.35-8.27) was also found to be a risk factor associated with early girl- child pregnancies. It was conclusion of the study was that being of apostolic religion, having financial problems and attending school away from home were risk factors associated with early girl-child pregnancies in Chidamoyo and Magunje areas of Hurungwe. Community awareness should be priority in Chidamoyo and Magunje areas of Hurungwe. So the identified multiple factors contributing to this problem can be used in formulating strategies to address the problem.